Spontaneous Bilateral Chylothorax Development During Alectinib Therapy for ALK-Rearranged NSCLC—A Case Report - Sunanjay Bajaj, MD; Andrew Chow, MD, PhD; Alexander Drilon, MD; Or Kalchiem-Dekel, MD (JTO Clinical and Research Reports, 2023)
The emergence of spontaneous nonmalignant chylous effusions during treatment with various tyrosine kinase inhibitors (TKIs) has been previously described; however, there have been no prior reports for alectinib. Herein, we report a case of symptomatic bilateral chylothorax during alectinib therapy in a patient with ALK-rearranged lung adenocarcinoma. Although immediate control of symptoms was achieved by placement of bilateral tunneled pleural catheters, the chylothorax ultimately resolved only after alectinib discontinuation and transition to an alternative TKI. This case adds alectinib to the growing list of TKIs that may be associated with the rare emergence of spontaneous, nonmalignant chylous effusions.